Extent of Usage of Credit Cards in Coimbatore - Choodambigai, S. Ramalinga (Indian Journal of Marketing, 2005)
Money lending is probably one of the oldest profession in the world. In India money lending has its origin in the vedic period and there are evidences of activities such as acceptance of deposits and lending of money states Manikandan (1997). According to Suneja (1988), the origin of money is rooted deeply in antiquity. In early primitive society, money (commodity money) took the form of cattle or a commodity depending upon various factors like the cultural and economic developments of a community, climate and location. This was the time when barter system was in prevalence. Then metals such as gold and silver were adopted as money for the purpose of exchange. Owing to the inconvenience, the metallic money was substituted with paper money (bank notes). Now in the present scenario paper money is being replaced by plastic money (credit cards) the world over.